Identifikasi Potensi Produk Pariwisata Sebagai Dasar Perencanaan Paket Wisata di Desa Cacaban Kidul Kabupaten Purworejo, Provinsi Jawa Tengah - Kurniati, Cucu; Josary, P. Jessica Jocelyn; Sinaga, Endang Komesty; Puksi, Faisal; Andrianto, Ronal (Politeknik Pariwisata NHI Bandung, 2023)
Desa Cacaban Kidul which is located in the vicinity of the Borobudur Temple development area has potential in the tourism sector in three forms, including the form of natural tourism potential, cultural tourism, craft/creative tourism, as well as non-tourism potential such as agricultural and livestock product potential. This research hopes to be able to provide specific benefits for the welfare of the community through an effort to develop communitybased tourism through community empowerment in Desa Cacaban Kidul. In conducting the research, the potential of the tourism products and the components of tourism products in terms of attractions, amenities and accessibility in Desa Cacaban Kidul are identified and analyzed. The result of the study can serve as an opportunity for a creation of tour package as it serves some recommendation for Desa Cacaban Kidul so that they can be managed properly and optimally as an effort to develop sustainable tourism through a series of tourism activities packaged in a tour package. Keywords: Tourism product, Tour Package Planning, Tourism Village